Protective effects of apigenin and myricetin against cisplatin-induced nephrotoxicity in mice - Samar M. Hassan; Marwa M. Khalaf; Sawsan A. Sadek; Amira M. Abo-Youssef (Taylor & Francis Group, 2017)
Context: Currently, the outcomes of the use of cisplatin in cancer therapy is limited by nephrotoxicity. Objective: This study aims to investigate the nephroprotective role of apigenin and myricetin against cisplatin-induced nephrotoxicity in mice. Materials and methods: Adult female Wistar Albino mice were divided into eight groups (n = 8). Group I served as normal control. Groups II, III and IV received apigenin (3 mg/kg, i.p.), myricetin (3 mg/kg, i.p.) or their combination respectively, for seven days. Group V served as positive control group, received vehicles for seven days and cisplatin (7.5 mg/kg, i.p.) for three days starting at day five. Groups VI, VII and VIII received apigenin, myricetin or their combination, respectively for seven days as well as cisplatin injection for three days starting at day five. by the end of the experimental period, a biochemical study involving, nephrotoxicity markers [serum creatinine (Cr) and blood urea nitrogen (BUN)], apoptotic marker [caspase 3], inflammatory mediators [tumour necrosis factor alpha (TNF-α), interleukin 6 (IL-6), cyclooxygenase I and II (COXI, COXII)] and oxidative stress biomarkers [malondialdehyde (MDA), reduced glutathione (GSH) and catalase] was conducted. In addition, renal histopathological alterations were evaluated. Results: Apigenin, myricetin and their combination significantly reduced blood BUN, serum Cr, caspase-3TNF-α, IL-6, COXI and COXII, MDA levels and significantly increased GSH level and catalase activity parallel to, histopathological improvement in kidney tissues. Discussion and conclusion: Apigenin and myricetin exhibited a protective and promising preventive strategy against cisplatin-induced nephrotoxicity due to their antioxidant and anti-inflammatory effects.